2002
DOI: 10.1089/152460902753645317
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Women's Choice of Obstetrician/Gynecologist

Abstract: A slight majority of these women, particularly those who are Hindu or Moslem or currently use a female, prefer female providers. Only a minority of these women feel strongly about their preference, and women with male providers are as satisfied as are women with female providers. Gender of provider was about as important as a physician's experience in choice of clinician.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 8 publications
4
39
0
Order By: Relevance
“…These traits were considered more important than clinical expertise. Zuckerman et al (2002) found striking gender preferences associated with patient religious practices in Brooklyn, New York. Female OB/GYNs were preferred by 56% of Protestants, 58% of Catholics and Jews, 74% of Hindus and 89% of Muslims.…”
Section: What Do Patients Prefer In Their Ob/gyn?mentioning
confidence: 99%
“…These traits were considered more important than clinical expertise. Zuckerman et al (2002) found striking gender preferences associated with patient religious practices in Brooklyn, New York. Female OB/GYNs were preferred by 56% of Protestants, 58% of Catholics and Jews, 74% of Hindus and 89% of Muslims.…”
Section: What Do Patients Prefer In Their Ob/gyn?mentioning
confidence: 99%
“…As a result, women may view men as being less likely to possess the personal attributes that make a good OB-GYN provider. Indeed, studies have shown that such personal attributes as being empathic and being skilled listeners are very important to women in choosing who to use as an OB-GYN provider (Chandler, Chandler, & Dabbs, 2000;Mavis et al, 2005;Zuckerman, Navizedeh, Feldman, McCalla, & Minkoff, 2002). Supporting the notion that women may believe that men are less likely to possess the attributes necessary to be a competent OB-GYN provider, Buck and Littleton (2014) found that women regarded typical male OB-GYN providers as awkward/uncomfortable when providing care whereas female OB-GYN providers were ascribed such attributes as easy to talk to and comfortable conducting physical exams.…”
Section: Stereotypes About Medical Students In Ob-gynmentioning
confidence: 99%
“…Studies carried out in the USA have found that only a minority of women felt strongly about their provider's gender and provider choice was more a function of other attributes such as experience, communication, style and technical expertise [6][7][8]. In contrast, another study undertaken in the United Kingdom showed that women's preferences change according to the particular problem or procedure in question: a female health professional is not important to most women when they are consulting about general problems, but is more important for screening for mammography and particularly important for gynaecological health problems [9].…”
Section: Client Preferences For Provider's Gendermentioning
confidence: 99%